Cognitive and physical performance are well preserved following standard blood donation: A noninferiority, randomized clinical trial. Issue Volume 60:Issue S3(2020) (1st June 2020) - Nadler, Roy; Tsur, Avishai M.; Lipsky, Ari M.; Lending, Gadi; Benov, Avi; Ostffeld, Ishai; Shinar, Eilat; Yanovich, Ran; Moser, Asher; Levy, Diana; Haiman, Nikolai; Eliassen, Hakon; et al.
Abstract : BACKGROUND: A walking blood bank (WBB) refers to the use of fellow combatants for battlefield blood donation. This requires pretesting combatants for infectious diseases and blood type. A fundamental prerequisite for this technique is that the donating soldier will suffer minimal physiological and mental impact. The purpose of the current study is to assess the effect of blood shedding on battlefield performance. METHODS: This is a double‐blind randomized control trial. Forty Israel Defense Forces combatants volunteered for the study. Participants underwent baseline evaluation, including repeated measurement of vital signs, cognitive evaluation, physical evaluation, and a strenuous shooting test. Three weeks after the baseline evaluation, subjects were randomized to either blood donation or the control group. For blinding purposes, all subjects underwent venous catheterization for the duration of a blood donation. Repeated vital signs and function evaluation were then performed. RESULTS: Thirty‐six patients were available for randomization. Baseline measurements were similar for both groups. Mean strenuous shooting score was 80.5 ± 9.5 for the control group and 82 ± 6.6 for the test group (p = 0.58). No clinically or statistically significant differences were found in tests designed to evaluate cognitive performance or physical functions. Vital signs taken multiple times were also similar between the test and control groups. CONCLUSIONS: Executive, cognitive, and physical functions were well preserved after blood donation. This study supports the hypothesis that a WBB does not decrease donor combat performance. The categorical prohibition of physical exercise following blood donation might need to be reconsidered in both military and civilian populations.